Study of heat transfer effect in Coupled Vane Compressor - Goh, Kean Kai Wen (Nanyang Technological University, 2022)
The Coupled Vane Compressor (CVC) was developed recently and features a compact design that reduces the amount of material used during production by roughly 40%. In a previous project, the development of 2D CFD using the overset meshing method was conducted. The overset mesh proved to be able to capture the flow details within the CVC to a fairly high level of accuracy. Using the same overset mesh, this project aims to study the behaviour of the fluid flow and heat transfer under varying wall temperatures of the CVC. It was uncovered that as wall temperature increased, a decrease in density, mass flow rate and heat loss from the working fluid was observed. On the other hand, average temperature of the working fluid during the compression cycle was seen to increase along with the wall temperature. Following, it is recommended that the simulation expands into a transient 3D simulation to better capture flow phenomenon within the CVC.